Effect of Baicalein on Cognitive Impairment in Diabetes Mellitus with Cerebral Small Vessel Disease - Li ZHOU; Zhengqi LU; Xiaoming YE; Wanxin YANG; Zhisheng WEI; Yi KONG; Xuming HUANG (康复学报)
Objective:To observe whether baicalein have therapeutic value on diabetes mellitus (DM) with cerebral small vessel disease (CSVD) so as to explore the pathogenesis and therapy of the cognitive ability and behavioral function disorder caused by chronic cerebral ischemia and hypoxia.Methods:A total of thirty male SD rats were randomly divided into normal control group, model group and treatment group, 10 rats in each group. After the stable models of DM with CSVD were established, cognitive function scores of all rats were evaluated by Morris water maze test, and the levels of acetylcholine (Ach) and acetylcholinesterase (AchE) in brain were assessed to evaluate the protective effects of baicalein.Results:Morris water maze test showed that learning and memory function had been significantly impaired in rats of DM with CSVD since the 7th day of modeling. Spatial probe test founded that the times of crossing platform in the model group were significantly lower than those in the normal control group (P<0.05). Compared with the normal control group, the Ach level in the brain homogenate of the model group reduced significantly (P<0.05), while the AchE level increased significantly (P<0.05). Compared with the model group, the Ach level in the brain homogenate of the treatment group increased significantly (P<0.05). The HE staining sections illustrated a large number of active neurons were found in the control group, but loose spongiform degeneration of brain tissue, apoptosis and necrosis of neurons and karyopyknosis were detected in the model group. However, it showed that the learning and memory abilities in the treatment group had improved, while the brain tissue also had been protected.Conclusion:Baicalein has a protective effect on cognitive impairment in diabetes mellitus with cerebral small vessel disease, and it may be a new targeted therapy for this disease.